Strategi Komunikasi Dakwah Kolaboratif di Era Digital : Studi Kasus Kolaborasi Influencer Muslim dan Lembaga Keislaman - Putri Handayani; Elvina Irma Yanti; Asma Yuleha; Safira Sammah; Muhammad Saleh (Universitas Maritim AMNI Semarang, 2025)
This research examines collaboration between Islamic institutions and Muslim influencers which can also have its own challenges. This is because the two parties have different goals, approaches and values ​​which of course can result in conflict and disruption of preaching. Another cause of challenges in da'wah is a lack of understanding in determining digital communication strategies. Moreover, we must not be left behind with developments because this can be a benchmark for success in collaborative da'wah in the era of digitalization. Therefore, it is necessary to have an appropriate da'wah strategy in order to achieve the effectiveness of da'wah. In this scientific journal, the method used is literature study. The literature method, or library research, is used to search for research information by reading scientific journals, digital book references, and published materials on the Internet. The only key to the success of da'wah development in this era is building a modern da'wah management strategy. The use of digital technology in da'wah content not only increases accessibility and reach but also creates better interaction between preachers and audiences.